Evaluation of Toxicological Risks and Effects of Microplastics on Nile Tilapia (Oreochromisniloticus) under in Vitro Laboratory Conditions - Macarius Pancras Mtega; Matobola Joel Mihale; Kessy Fidel Kilulya (East African Journal of Biophysical and Computational Sciences)
Microplastics have been reported by many literatures as contaminants of environmental water bodies and are ingested by aquatic organisms due to their small sizes. Knowing the effects of microplastics to fresh water fish which are kept in ponds helps in managing fish keeping practice. The objective of research was to determine the toxicity of microplastics to Nile tilapia (Oreochromis niloticus). The Experiment was done in 80 fish samples. Microplastics which were prepared for the batch experiment were introduced in the aquarium followed with observation for 21 days. The digestion of fish gills and intestines involved 10 mL of 10% (w/v) KOH solution and incubation at 65oC for 24 hours. Engulfed microplastics were determined using stereo microscope and At-IR spectrophotometer for confirmation. Engulfed microplastics were observed to be in mean range of 3.37 x 102±4.04 x 102 to 2.32 x 103 ± 3.57 x 103 particles/kg in gills and 4.68 x 104 ± 3.02 x 104 to4.40 x 104 ± 5.34 x 104 particles/kg in intestines. The observed responses were loss of equilibrium for 35% of fish, abnormal swimming for 49% of fish, abnormal ventilator behavior for 59% of fish, abnormal appearance for 39% of fish and average growth weight increase in control experiment fish was 6.10±2.62 g compared to 1.7 ± 3.62 g in test fish. There was no mortality of Nile tilapia. The responses of fish to the presence of microplastics in aquarium indicated that microplastics had adverse effects to Nile tilapia (Oreochromis niloticus). More researches have to be done on fish physiological changes caused by microplastics.